Cross Talk between Proliferative, Angiogenic, and Cellular Mechanisms Orchestred by HIF-1α in Psoriasis - Azael Torales-Cardeña; Isaí Martínez-Torres; Sandra Rodríguez-Martínez; Fernando Gómez-Chávez; Juan C. Cancino-Díaz; Ernesto A. Vázquez-Sánchez; Mario E. Cancino-Díaz (Mediators of Inflammation)
Psoriasis is a chronic inflammatory skin disease where the altered regulation in angiogenesis, inflammation, and proliferation of keratinocytes are the possible causes of the disease, and the transcription factor “hypoxia-inducible factor 1-alpha” (HIF-1α) is involved in the homeostasis of these three biological phenomena. In this review, the role of HIF-1α in the cross talk between the cytokines and cells of the immunological system involved in the pathogenesis of psoriasis is discussed.